OPTIMIZATION OF PHARMACEUTICAL CARE FOR JUVENILE RHEUMATOID ARTHRITIS AT THE REGIONAL LEVEL - A. A. Skripko; L. N. Geller; G. G. Radnaev; Т. V. Hadanova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2018)
Clinical practice and content analysis of scientifi c literature indicate that for treatment of the immune-infl amatory disease called juvenile rheumatoid arthritis (JRA), the use of only basic medicines (BM) is not suffi cient.The aim of the study is the organization of pharmacotherapy of JRA patients by genetically engineered biological preparations (GEBP), affecting the immune processes of the body directly.Materials and methods: the theory of marketing, content analysis, the ABC-analysis, sociological survey, pharmacoeconomic methods.Results and discussion. Depending on the individual characteristics of patients, the clinical picture of the disease can manifest itself in different ways, which requires justifi cation of the necessary schemes of GEBP pharmacotherapy at each stage of the carried out treatment. In the course of studying the organization of pharmaceutical assistance at the inpatient stage, we carried out a content analysis of 175 medical records of the patients (aged 2-17 years old) of the cardiologic department of Irkutsk State Children's Clinical Hospital, in the dynamics of a few years (2015-2017), and the expert assessment of the degree of GEBP demand was carried out by the doctors. The analysis of the pharmacotherapy has shown that GEBP is used as monotherapy in patients with intolerance to basic medicines or to combinations with basic medicines. It is irrational to start the GIBP treatment immediately because of possible side effects and their high cost. According to the content analysis of the reports of the regional Ministry of Health on preferential drug provision of handicapped children, both in hospital and at outpatient treatment stage, the pharmacotherapy schemes including Adalimumab, Abatacept, Infl iximab, Tocilizumab, Etanercept are most in demand.Conclusion. The study of the organization of GEBP pharmacotherapy, the expert assessment carried out by the doctors, the results of the marketing analysis of the regional pharmaceutical market made it possible to substantiate and propose a rational assortment portfolio of this group of medicines for treatment of various JRA options, taking into account the price component in the Irkutsk region. The obtained results can be used for the formation of the medicinal budget of medical organizations in the region.